2016
DOI: 10.22159/ijpps.2016.v8i9.13590
|View full text |Cite
|
Sign up to set email alerts
|

Exaggeration of Type 2 Diabetes Due to Caffeine-Nicotine Co-Administration: A Study in Rats

Abstract: <p><strong>Objective: </strong>This study evaluated the toxic effect of simultaneously injected normal doses of caffeine and nicotine in diabetic lab animals.</p><p><strong>Methods: </strong>A study was conducted for three weeks in seven rat groups (n=6); viz. first non-diabetic group treated with caffeine (20 mg/kg, ip) twice daily, second with nicotine (0.4 mg/kg, ip) twice daily and third with both treatments simultaneously; whereas other three groups treated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…This research protocol was continuation of our previous work Kumbhar et al where we demonstrated exaggeration of Type 2 diabetes by caffeine nicotine coadministration in diabetic rats [7]. We also conducted another study where we proposed significant antidiabetic activity of CI extract in SD rats [15].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…This research protocol was continuation of our previous work Kumbhar et al where we demonstrated exaggeration of Type 2 diabetes by caffeine nicotine coadministration in diabetic rats [7]. We also conducted another study where we proposed significant antidiabetic activity of CI extract in SD rats [15].…”
Section: Discussionmentioning
confidence: 52%
“…In our previous study, we demonstrated exaggeration of streptozotocin (STZ)-induced Type 2 diabetes in rats due to caffeine-nicotine coadministration [7]. When we compared diabetic control group with coadministration group we observed increase in insulin resistance, hyperglycemia, and hyperlipidemia.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Konsumsi kafein dan nikotin secara bersamaan dapat meningkatkanaresistensi ainsulin. aDalam penelitianayanga dilakukan oleh Khumbar terhadapa mencit didapatkan hasil bahwa nikotin dan kafein yang merupakan sistem obat perangsang apabila diinjeksikan secara bersamaan dapat mengakibatkan kerusakan adiktif (Kumbhar et al, 2016).…”
Section: Pendahuluanunclassified